psychology-cognition 2016
DOI: 10.35841/psychology-cognition.1.1.64-69
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Automatic Thoughts Questionnaire-18 item- Multiple Sclerosis-Arabic (ATQ-18-MS-Ar) among multiple sclerosis patients.

Abstract: Objective: Our study has validated the Automatic thoughts Questionnaire among Syrian multiple sclerosis patients. The Automatic Thoughts Questionnaire-18 item-Multiple Sclerosis-Arabic has included both the version of the 8-item Negative Automatic Thoughts Questionnaire and 10 positive items from the Automatic Thoughts Questionnaire-Revised. Method: A total of 65 Syrian multiple sclerosis patients have been recruited in Damascus Hospital and Ibn Alnafees Hospital for validation of Automatic Thought Questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Assess the prevalence rates of thoughts, feelings, and behaviors among Syrian in War conditions: evaluate the frequency of depression, two main depressive symptoms of DSM-IV (depressive mood and an hedonia), suicidal behavior, negative and positive automatic thoughts, anxiety, stress, self-esteem and satisfaction with lifein non-clinical and clinical samples in War conditions in Syria. [10,[12][13][14]; BDI-FS-Ar(Beck Depression Inventory-Fast Screen-Arabic) [4]; ATQ-18-Ar (Automatic Thoughts Questionnaire-18 item-Arabic) [2]; MADRS-S-Ar (Montgomery-Asberg Depression Rating Scale Selfassessment-Arabic) [15,16]; BDI-II (Beck Depression Inventory-II) [17], DASS-21 (Depression Anxiety Stress Scale-21) [18,19], RSES (Rosenberg self-esteem scale) [20], and SWLS (Satisfaction with life scale) [4,10,21] were used in this study.…”
Section: Bmentioning
confidence: 99%
See 1 more Smart Citation
“…Assess the prevalence rates of thoughts, feelings, and behaviors among Syrian in War conditions: evaluate the frequency of depression, two main depressive symptoms of DSM-IV (depressive mood and an hedonia), suicidal behavior, negative and positive automatic thoughts, anxiety, stress, self-esteem and satisfaction with lifein non-clinical and clinical samples in War conditions in Syria. [10,[12][13][14]; BDI-FS-Ar(Beck Depression Inventory-Fast Screen-Arabic) [4]; ATQ-18-Ar (Automatic Thoughts Questionnaire-18 item-Arabic) [2]; MADRS-S-Ar (Montgomery-Asberg Depression Rating Scale Selfassessment-Arabic) [15,16]; BDI-II (Beck Depression Inventory-II) [17], DASS-21 (Depression Anxiety Stress Scale-21) [18,19], RSES (Rosenberg self-esteem scale) [20], and SWLS (Satisfaction with life scale) [4,10,21] were used in this study.…”
Section: Bmentioning
confidence: 99%
“…correlated with positive thinking and inversely correlated with negative thinking [2,9]. Before the War in Syria, in a studydonein1999 and published in 2003, Radwan [3] found that severe depression using BDI-II affects 5.4% of Damascus University students [3,4], 5.7 in males and 5.5% in females.…”
mentioning
confidence: 99%